Evangelism in the modern world - Thomson, D. P. (Handbooks of modern evangelism, 1924)
The place of evangelism in the modern world, by Principal A.E. Garvie.--Evangelism and the church of to-day, by Rev. J. Harry Miller.--Evangelism and the higher criticism, by Professor George Jackson.--Evangelism and the new psychology, by Principal Henry Townsend.--Evangelism and the materialistic spirit of the age, by Rev. Frederic C. Spurr.--The approach to the modern mind, by Dr. John Douglas Adam.--Sin in the preaching of to-day, by Rev. W. Mackintosh Mackay.--The preaching of the cross, by Principal W.M. Clow.--The Kingdom of God in evangelism, by Rev. A. Herbert Gray.--The present opportunity for evangelism, by Rev. E. Aldom French.